IMRT with Stereotactic Body Radiotherapy Boost for High Risk Malignant Salivary Gland Malignancies: A Case Series - Karam, Sana D.; Rashid, Abdul; Snider, James W.; Wooster, Margaux; Bhatia, Shilpa; Jay, Ann K.; Newkirk, Kenneth; Davidson, Bruce; Harter, William K. (Frontiers in Oncology, 2014)
Patients with high risk salivary gland malignancies are at increased risk of local failure. We present our institutional experience with dose escalation using hypofractionated stereotactic body radiotherapy (SBRT) in a subset of this rare disease. Over the course of 9 years, 10 patients presenting with skull base invasion, gross disease with one or more adverse features, or those treated with adjuvant radiation with three or more pathologic features were treated with intensity-modulated radiation therapy followed by hypofractionated SBRT boost. Patients presented with variable tumor histologies, and in all but one, the tumors were classified as poorly differentiated high grade. Four patients had gross disease, three had gross residual disease, three had skull base invasion, and two patients had rapidly recurrent disease (≤6 months) that had been previously treated with surgical resection. The median stereotactic radiosurgery boost dose was 17.5 Gy (range 10–30 Gy) given in a median of five fractions (range 3–6 fractions) for a total median cumulative dose of 81.2 Gy (range 73.2–95.6 Gy). The majority of the patients received platinum based concurrent chemotherapy with their radiation. At a median follow-up of 32 months (range 12–120) for all patients and 43 months for surviving patients (range 12–120), actuarial 3-year locoregional control, distant control, progression-free survival, and overall survival were 88, 81, 68, and 79%, respectively. Only one patient failed locally and two failed distantly. Serious late toxicity included graft ulceration in one patient and osteoradionecrosis in another patient, both of which underwent surgical reconstruction. Six patients developed fibrosis. In a subset of patients with salivary gland malignancies with skull base invasion, gross disease, or those treated adjuvantly with three or more adverse pathologic features, hypofractionated SBRT boost to intensity-modulated radiotherapy yields good local control rates and acceptable toxicity.